ANXIETY REDUCTION EFFORTS TO MOTHER WITH BABY IN HIGH RISK PERINATAL ROOM THROUGH THERAPEUTIC COMMUNICATION - Oktaviani, Putri; Suprihatin, Suprihatin (Jurnal Penelitian STIKES Kediri, 2013)
Mothers will experience anxiety when a baby has a critical health condition and should be treated in intensive care. The purpose of this study to analyze the effect of therapeutic communication in decreasing mothers anxiety levels with infant in high-risk perinatal. The research design was pre-experimental one group pre-post test design. Population is mothers with babies who were treated in a high-risk perinatal, as many as Â 20 respondents, samples were taken with a total sampling method for a month, data taken through a structured interview. Given intervention is therapeutic communication with the variable being measured maternal anxiety. Analyst with the Wilcoxon Signed Ranks Test with Î±Â£0.05. The results showed maternal anxiety levels before treatment were 50% and 65% after light treatment, and the results of statistical test obtained p = 0.001 which showed there is significant effect of giving therapeutic communication in reducing maternal anxiety. It was concluded that giving therapeutic communication by nurses can reduce the level of mothers anxiety with babies in intensive care.